Potential for Nuclear Medicine Therapy for Glioblastoma Treatment - Bailly, Clément; Vidal, Aurelien; Bonnemaire, Coralie; Kraeber-Bodéré, Françoise; Chérel, Michel; Pallardy, Amandine; Rousseau, Caroline; Garcion, Emmanuel; Lacoeuille, Franck; Hindré, François; Valable, Samuel; Bernaudin, Myriam; et al. (Frontiers in Pharmacology, 2019)
Glioblastoma is the most common malignant adult brain tumor and has a very poor patient prognosis. The mean survival for highly proliferative glioblastoma is only 10 to 14 months despite an aggressive current therapeutic approach known as Stupp's protocol, which consists of debulking surgery followed by radio- and chemotherapy. Despite several clinical trials using anti-angiogenic targeted therapies, glioblastoma medical care remains without major progress in the last decade. Recent progress in nuclear medicine, has been mainly driven by advances in biotechnologies such as radioimmunotherapy, radiopeptidetherapy and radionanoparticles, and these, bring a new promising arsenal for glioblastoma therapy. For therapeutic purposes, nuclear medicine practitioners classically use β- particle emitters like 131I, 90Y, 186/188Re or 177Lu. In the glioblastoma field, these radioisotopes are coupled with nanoparticles, monoclonal antibodies or peptides. These radiopharmaceutical compounds have resulted in a stabilization and/or improvement of the neurological status with only transient side effects. In nuclear medicine, the glioblastoma localized and targeted internal radiotherapy proof-of-concept stage has been successfully demonstrated using β- emitting isotopes, Similarly, α particle emitters like 213Bi, 211At or 225Ac appear to be an innovative and interesting alternative. Indeed, α particles deliver a high proportion of their energy inside or at close proximity to the targeted cells (within a few micrometers from the emission point versus several millimeters for β- particles). This physical property is based on particle-matter interaction differences and results in α particles being highly efficient in killing tumor cells with minimal irradiation of healthy tissues and permits targeting of isolated tumor cells. The first clinical trials confirmed this idea and showed good therapeutic efficacy and less side effects, thus opening a new and promising era for glioblastoma medical care using α therapy. The objective of this literature review is focused on the developing field of nuclear medicine and aims to describe the various parameters such as targets, vectors, isotopes or injection route (systemic, local) in relation to the clinical and preclinical results in glioblastoma pathology.